2022
DOI: 10.1111/1750-3841.16232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin E supplementation levels on growth performance, breast muscle meat quality characteristics, and fatty acid composition of geese

Abstract: This study investigated the effects of dietary supplementation with vitamin E (VE) on the growth performance, breast muscle quality, fatty acid (FA) composition, and muscle fiber characteristics of geese. In the present study, a total of 240 healthy 29‐day‐old male Jiangnan white geese were randomly divided into six experimental groups, with five replicates in each group and eight geese in each replicate. Group A, the control group, was fed a basal diet; Groups B, C, D, E, and F were fed diets supplemented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…One study found that, compared with the control group, broilers fed an AFB 1 ‐contaminated diet had poor meat quality, which manifested as an increase in shear force (Chen et al., 2022). It was found that the addition of antioxidants, such as vitamins, can directly or indirectly remove excess free radicals generated in the body, decrease polyunsaturated fatty acid (PUFA) oxidation, and reduce lipid oxidation (Yang et al., 2022). The use of certain plants or plant extracts in diets as antioxidants has become a hot topic in current research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that, compared with the control group, broilers fed an AFB 1 ‐contaminated diet had poor meat quality, which manifested as an increase in shear force (Chen et al., 2022). It was found that the addition of antioxidants, such as vitamins, can directly or indirectly remove excess free radicals generated in the body, decrease polyunsaturated fatty acid (PUFA) oxidation, and reduce lipid oxidation (Yang et al., 2022). The use of certain plants or plant extracts in diets as antioxidants has become a hot topic in current research.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the addition of antioxidants, such as TA B L E 4 Effects of lycopene on glutathione (GSH) concentration and GSH peroxidase (GSH-Px) and GSH s-transferase (GST) and GSH reductase (GR) activities of breast muscle in broilers. vitamins, can directly or indirectly remove excess free radicals generated in the body, decrease polyunsaturated fatty acid (PUFA) oxidation, and reduce lipid oxidation (Yang et al, 2022). The use of certain plants or plant extracts in diets as antioxidants has become a hot topic in current research.…”
Section: The Effect Of Lycopene On the Meat Quality Of Broilersmentioning
confidence: 99%